Structural Behaviour of Multi-Storey Building for Different Plan Configuration - Bhawendra Nath Yogi; Dr. M. P. Verma (International Journal of Scientific Research in Civil Engineering, 2022)
Seismic analysis of a multi-story Reinforced concrete frame is analyzed under moderate earthquake loads as an application of seismic hazard and in accordance with the seismic provisions proposed in IS: 1893-2002 to analyze the performance of existing buildings if exposed to seismic loads. The frame was analyzed using the response spectrum method to calculate the seismic displacements and stresses. The behavior of Multi-story building of regular and irregular plan configuration under earthquake is complex and it varies of wind loads are assumed to act simultaneously with earthquake loads.The study of this research mainly emphasize the structural behavior of multi-storey building for different plan configuration such as regular building along with L- shape and I- shape. In this modeling of G+ 24 storey RCC framed building is studied for earthquake load using STAAD-PRO V8i. Assuming that material property is linear static and dynamic analysis is performed. These analyses are carried out by considering different seismic zones (III and V) and for each zone the behavior is assessed by taking three different types of soils namely Hard, Medium and Soft. Post analysis of the structure, lateral displacements, story drift, base shear, maximum bending moment and design results are computed and then compared for all the analyzed cases. Designs of these structures in all cases are also done to obtain the most economic structure above all the cases.
Keywords: Structural Analysis And Design; High Rise Building; Response Spectrum; Plan Irregularity; STAAD-Pro V8i